ChemInform Abstract: One‐Pot Synthesis of N‐Substituted 2, 4‐Thiazolidinediones and Computational Investigation of the Products. Issue 29 (1st July 2013) - Asghari, Sakineh; Haghdadi, Mina; Ahangar, Savia Momeni; Ramezani, Samaneh
Abstract The three‐component reaction of acetylenic esters (I) or (V), 2, 4‐thiazolidinedione (II), and tert‐butyl isocyanide (III) is studied.